Influencing factors of sports tourism safety accidents in Tibet, China: fsQCA analysis based on the SCM - Kejun Wu; Aoxue Xing; Jingbo Zhou; Lihui Su; Sen Zhang; Shuanyan Yang (PLoS ONE, 2025)
A comprehensive analysis of the systemic causes of safety accidents in sports tourism on the Qinghai-Tibet Plateau is significant for high-quality development. Utilizing 32 verified accident cases (2010–2025) in the Tibet Autonomous Region of China, this study extracted six critical factors through content analysis: organizational professionalism, rescue capacity, management systems, natural environment, tourist vulnerability, and tourist behavior. The Swiss Cheese Model (SCM) analyzed latent/active failures through case reports and regional environmental data, while the fuzzy-set Qualitative Comparative Analysis (fsQCA) deciphered nonlinear configuration paths across six factors. The results reveal that sports tourism accidents in Tibet arise from the coupling of multiple factors. Specifically, the combination of six influencing factors constitutes the causal paths for severe and general accidents. Among these factors, environmental factors and tourist characteristics are key contributors to accidents. Based on these findings, it is essential to establish a sports tourism risk prevention system for Tibet, which should comprise four layers: natural defense, behavioral defense, managerial defense, and rescue defense. This study deepens the understanding of sports tourism safety accidents on the Qinghai-Tibet Plateau. It integrates the SCM and the fsQCA method, contributing to sports tourism safety research. The proposed risk prevention system provides useful references for local safety management. Future research can focus on the dynamic changes of influencing factors and test the research framework and risk prevention system’s applicability in other similar areas.